(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
This article analyzes the significance of using the FILA table in teaching phthisiology to develop clinical thinking in medical students. The FILA table is considered a tool that facilitates a deeper understanding of the learning process and enhances students’ problem-solving skills in clinical settings. This method plays a crucial role in shaping clinical analysis skills, developing critical thinking and encouraging students to make independent decisions. By using the FILA table, students can systematically analyze existing information about diseases, deepening their knowledge. Furthermore, this tool increases the effectiveness of interactive methods in medical education by directing students toward the practical application of theoretical knowledge. The study examines the effectiveness of this approach, methods of its implementation, and its impact on the educational process. The relevance of the FILA table in the learning process is emphasized, including its use in practical training, its connection with real clinical cases, and the opportunities it provides for students to conduct independent research.